Delphi technique for generating criteria and indicators in monitoring ecotourism sustainability in Northern forests of Iran: Case study on Dohezar and Sehezar Watersheds - Barzekar, Godratollah; Aziz, Azlizam; Mariapan, Manohar; Ismail, Mohd Hasmadi; Hosseni, Syed Mohsen (2011)
Ecotourism is widely accepted as the most effective type of sustainable development. For monitoring ecotourism sustainability in the Northern forest of Iran, a study was designed to help identifying criteria and indicators (C&I) with the principle goal to ensure the objectives of forest management, and at the same time – maintain processes in a sustainable manner. Indicators act as an instrument which can be used for monitoring sustainability. Hence indicators should be multidisciplinary, and cover all aspect of social, ecological, cultural, economic and institutional factors affecting sustainability of ecotourism. In this study, C&I were identified by using the Delphi approach through multidisciplinary panel team. Three rounds of meetings were held for discussions and dissemination of research to a panel of local experts. At the end of the second round we reached a consensus on 9 criteria and 61 indicators, which include 21 indicators related to ecological aspects, 8 to economic aspects, 21 to social aspects, 6 to cultural aspects and 5 to institutional aspects. The selected indicators would be applied by the Iranian Cultural, Heritage, Handicrafts and Tourism Organization for monitoring ecotourism sustainability in the Northern forest of Iran.